Prevalence of self-medication practices among the residents of urban slums located near govt. medical college, Jabalpur - Jain, Shubham; Thakur, Aditya; Peepre, Kunal; Kaushal, Shivika; Kasar, Pradeep (International Journal Of Community Medicine And Public Health, 2018)
Background: Self-medication is defined as medication taken on the patient’s own initiative or on the advice of pharmacist or any other lay person. Self-medication can be described as a double edged sword for its users, because it has both beneficial and harmful effects. According to recent community based study in 2016 prevalence of self-medication in developing countries varies from 12% to as high as 73% in different communities. The objectives of the study were to assess the prevalence of self-medication among the residents of urban slums located near Govt. medical college, Jabalpur and to identify the factors associated with the practice of self-medication. Methods: It was a descriptive cross sectional study conducted in 412 families residing in slum areas around the medical college for duration of 2 months [1st July to 31st august 2017]. One participant from each family was interviewed. Data on socio demographic details (age, gender, education, occupation, and income), practice of self-medication, and reasons for use of self-medication were collected. Results: Among the total 412 participants, 176 (42.7%) practiced self-medication out of which 43.6% were Females. Highest prevalence of 58.1% amongst 18-40 years of age group, 69.3% was literates. Major reason for self-medication being disease is simple (56.5%). Majority took self-medication occasionally (72.5%) and most common source were Pharmacists (87.42%) through OTC (81.14%). Most widely used drugs were Analgesics (66.28%) and main indications were headache, body ache and other pains (25.2%). Associations were compared with chi-square test Socio economic status of participants and Vicinity distance from hospital revealed statistically significant result. Socio-economically upper class (p꞊0.018) and participants living more than 500 m away from hospital (p=0.010) tends to take more self medication. Conclusions: There was a heterogeneous spread in the practices. Easy availability of over the counter (OTC) drugs is a major factor responsible for irrational drug use. Community awareness programme, educational interventions should be conducted about side effects of self-medication.